RANCANG BANGUN ENTERPRISE RESOURCE PLANNING UNTUK MENUNJANG KEGIATAN BISNIS DI TOKO AMIN - Veri Yanto; Pintubipar Saragih, Saut (LPPM Universitas Putera Batam, 2022)
ERP (enterprise resource planning) is an excellent processing system for companies and organizations that exist today, ERP is becoming very widely used by companies because it is very helpful in processing companies from product processing to finance. Research is to create an ERP system based on problems in the store, the main issue in this store is the goods processing system which is still manual and ineffective. Data collection methods used are interviews at the research site and observations at the store to find out the problems. The method of the research uses the waterfall method. This system can solve problems that arise in the processing of goods for shop owners.